The existence and strategy of planting Bengawan rice in ecoleta farmers, Detusoko District, Ende Regency - Bunga, Bunganus Maurits (Journal of Social Science, 2023)
Research entitled The Existence and Cultivation Strategy of Bengawan Rice for Ekoleta Farmers, Detusoko District, Ende Regency. Focuses on how the strategy of the Ekoleta rice farming community maintains the existence of Bengawan rice, using the theory of Community Empowerment according to Robert Chambers. This study aims to determine the strategy of Ekoleta rice farmers in maintaining the existence of Bengawan Ekoleta rice. In accelerating these goals, the researchers used descriptive qualitative research methods, and for data collection using interviews, observation, and documentation techniques. Researchers found several strategies of Ekoleta rice farmers in maintaining the existence of Bengawan Ekoleta rice, namely through the selection of seeds and nurseries, rice casings, and rice care. The findings above are very relevant when linked to the theoretical basis of community empowerment according to Robert Chambers, namely Ekoleta rice farmers empower themselves through Bengawan rice farming activities in new ways that keep them cultivating Bengawan Ekoleta rice. In the end, the researcher recommends a number of suggestions: for the Ekoleta rice farming community to continue to maintain the existence of bengawan rice so that this bengawan rice will continue to exist at any time.